Prostate cancer detection with biparametric magnetic resonance imaging (bpMRI) by readers with different experience: performance and comparison with multiparametric (mpMRI) - Gatti, Marco; Faletti, Riccardo; Calleris, Giorgio; Giglio, Jacopo; Berzovini, Claudio; Gentile, Francesco; Marra, Giancarlo; Misischi, Francesca; Molinaro, Luca; Bergamasco, Laura; Gontero, Paolo; Papotti, Mauro; et al. (Abdominal imaging, 2019)
Purpose To study the detection of clinically significant prostate cancer (PCa) by readers with different experience, comparing performance with biparametric magnetic resonance imaging (bmMRI) and with the reference multiparametric (mpMRI). Methods Retrospective analysis of 68 patients with mpMRI of the prostate at 1.5 Tesla using a 32 phased-array coil. Forty-five patients (cases) underwent radical prostatectomy, whereas 23 (controls) had a negative prostate biopsy and ≥ 2.5 years of negative follow-up. Six observers (two with 1000 cases interpreted, two with 300, two with 100) performed the analysis first with bpMRI including diffusion-weighted imaging (DWI), apparent diffusion coefficient (ADC) maps and T2-weighted (T2W) imaging in three planes and, after 1 month, with mpMRI, adding dynamic contrast enhancement (DCE). The performance was quantified by sensitivity (SNS), specificity (SPC) and area under the curve (AUC) of the ROC (Receiver Operating Characteristics) procedure. Results Concordance within observers of equivalent experience was good (weighted Cohen’s k ≈ 0.7). The two expert readers performed as well in bpMRI as in mpMRI (SNS = 0.91–0.96, AUC = 0.86–0.93; p ≥ 0.10); readers with 300 cases performed well in mpMRI, but significantly worse in bpMR: SNS = 0.58 versus 0.91 ( p < 0.0001) and AUC = 0.73 versus 0.86 ( p = 0.01); the limited experience of readers with 100 cases showed in mpMRI (SNS = 0.71; AUC = 0.77) and even more in bpMRI (SNS = 0.50; AUC = 0.68). Conclusion The study revealed the impact of the readers’ experience when using bpMRI. The bpMRI without contrast media was a valid alternative for expert readers, whereas less experienced ones needed DCE to significantly boost SNS and AUC. Results indicate 700–800 cases as threshold for reliable interpretation with bpMRI.